All about Flowers : James Vick's Nineteenth-Century Seed Company - Mickey, Thomas J. (Book collections on Project MUSE., 2021)
"A nineteenth-century entrepreneur's bold, innovative marketing helped transform flower gardens into one of America's favorite hobbies. There is much in this sin-plagued world of ours; and, had we no flowers, I believe existence would be hard to be born. So states a customer's 1881 letter-one of thousands James Vick regularly received. Vick's business, selling flower seeds through the mail, wasn't unique, but it was wildly successful because he understood better than his rivals how to engage customers' emotions. He sold the love of flowers along with the flower seeds. Vick was genuinely passionate about floriculture, but he also pioneered what we now describe as integrated marketing. He spent a mind-boggling $100,000 per year on advertising (mostly to women, his target demographic); he courted newspaper editors for free publicity; his educational guides presaged today's content marketing; he recruited social influencers to popularize neighborhood gardening clubs; and he developed a visually rich communication and branding strategy to build customer loyalty and inflect their purchasing needs with purchasing desire"--